PENDIRIAN PERSEROAN KOMANDITER DI DENPASAR - Tirta Sari Dew, I Gst. Ag.; Wiryawan, I Wayan; Rudy, Dewa Gde (Kertha Semaya : Journal Ilmu Hukum; Vol. 01, No. 06, Juli 2013)
This writing be given the title of establishment liability commanditaire vennootschap in Denpasar. As for the purpose of writing is for know the requirements within the establishment liability commanditaire vennootschap in Denpasar. Methods research which used is research method juridical empirical. The establishment of a limited partnership organized under Article 19 of the Code of Commercial Law (to businesses). The establishment of a limited partnership in Denpasar generally by notarial deed. Deed of establishment limited partnership includes the identity of the founder, the determination name limited partnership, a description of the limited partnership that is general or limited, clausula-clausula Another important with regard to third party against allies founder, Formation cash (money) of a limited partnership registration certificate of establishment to the District Court.
Keywords: Commanditaire Vennootschap, Juridical Empirical, Notary Deed